The christian world - Brown, Alan (Hodder Wayland London, 2001)
Christianity is the world's largest religion. Almost 1,500 million people belong to its many different groups. This book looks at first Christians, and traces the customs and beliefs of today's four great families: Orthodox, Roman Catholic, Protestant and Pentecostal. It also explains why the centre of faith for Christians is Jesus, the Christ.